Major contributors to FLASH sparing efficacy emerge from murine skin studies: dose rate, total dose per fraction, anesthesia and oxygenation - Pogue, Brian W.; Thomas, William S.; Tavakkoli, Armin D.; Jarvis, Lesley A.; Hoopes, P. Jack (Frontiers in Oncology, 2024)
BackgroundNormal tissue sparing from radiation damage upon ultra-high dose rate irradiation, known as the FLASH effect with an equivalent tumor response, has been widely reported in murine skin models, and translation of this type of radiotherapy to humans has already begun, with skin sparing being a primary outcome expected.MethodsThis study reviews the status of the field, focusing on the proposed mechanisms and skin response assays, outlining what has become known in terms of input parameters that might control the magnitude of the FLASH effect.ResultsMurine studies have largely focused on acute damage responses, developing over 3–8 weeks, to single doses of FLASH versus conventional dose rate (CDR), suggesting that at dose rates above tens of Gray per second, with a total dose of more than 20 Gy, the FLASH effect is induced. Fractionated delivery appears to be possible, although fraction sizes >17 Gy appear to be needed for sparing efficacy. The interplay between the dose rate and total dose per fraction remains to be fully elucidated. Oxygen is a modulator of efficacy, with both hypoxia and hyperoxia diminishing the effect of FLASH. Measurement of transient changes in oxygen levels is possible and may be a marker of treatment efficacy.ConclusionTaken together, murine skin data provide important information for translational studies, despite the associated limitations. Studies of later-term sparing effects, as well as studies on pig skin, are needed to take the next step in assessing translational FLASH efficacy. The control of biological factors, such as tissue oxygenation, may be required to understand and control the response.